2010
DOI: 10.1248/yakushi.130.215
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Effect of Stress Preconditioning in Restrain Stress-induced Behavioral Alterations

Abstract: Stress preconditioning has been documented to confer on gastroprotective eŠects on stress-induced gastric ulcerations. However, the eŠects of prior exposure of stress preconditioning episodes on stress-induced behavioral changes have not been explored yet. Therefore the present study was designed to investigate the ameliorative eŠects of stress preconditioning in immobilization stress-induced behavioral alterations in rats. The rats were subjected to restrain stress by placing in restrainer (5.5 cm in diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…These alterations can play an important role in the onset and maintenance of wasting found in the DOXO treatment. A study performed by Kaur et al [29] showed that rats subjected to restraint stress demonstrated a reduction of locomotor and exploratory activity. Liu et al [30] showed similar results in the chronic, unpredicted mild stress in rats.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations can play an important role in the onset and maintenance of wasting found in the DOXO treatment. A study performed by Kaur et al [29] showed that rats subjected to restraint stress demonstrated a reduction of locomotor and exploratory activity. Liu et al [30] showed similar results in the chronic, unpredicted mild stress in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Impact of acute stress has been previously shown to affect behavioral patterns in rodents, in a nonconventional manner as well. For instance, although most studies in rodent report decrease exploration/activity in the open field test in response to restraint stress [50][51][52][53], another study has reported the opposite effect [52] suggesting that in certain contexts (especially very shortly following restraint stress) acute stress can temporarily increase exploration in the open field test. Furthermore, acute stress paradigms including restraint stress can cause reduction in anxietylike behaviors such as risk assessment behaviors (head poking and stretch attempts) and at the same time cause increases in the frequency of direct entries in the inner/anxiogenic zone of a novel environment such as the open field [54].…”
Section: The Paradoxical 'Anxiolytic' Effect Of Acute Stressmentioning
confidence: 99%
“…This phenomenon is known as preconditioning [26]. Hyperbaric oxygen [26], short ischemia [2729], small doses of lipopolysaccharides [30], restraint stress [31], hypoxia [32], hyperthermia [32] and moderate aerobic exercise [33,34] are some of the stimuli producing preconditioning. We chose the example of exercise to explain the role of reactive species on preconditioning (see Figure 3).…”
Section: Physiological Effects Of Reactive Speciesmentioning
confidence: 99%